The Effect of Lunges Jump Training on Back Kick Technique of Kabaddi Athletes - Amelia Vega; Dhias Fajar Widya Permana (Universitas Negeri Semarang, 2026)
Observations of kabaddi players or athletes in Central Java reveal weaknesses in applying this technique on the field, particularly regarding maintaining a safe distance and strength. This study aims to explore the effect of lunge jump training on the back kick technique used by Kabaddi players in Central Java Province in 2025. This study is a quantitative study using an experimental method. It employs a one-group pre-test and post-test design. The study involved 30 kabaddi athletes in Central Java as the sample or research subjects. The instrument used in this study was a test to measure the distance of backward kicks. The data analysis techniques in this study include prerequisite tests: normality and homogeneity tests, and hypothesis testing: the Paired Sample T-Test. The results of this study show that the average backward kick distance during the pre-test was 72.45 cm, and the average backward kick distance during the post-test was 79.20 cm.The normality test results showed that the data had a normal distribution (p > 0.05), and the homogeneity test proved that the variance of the data was consistent. The paired sample t-test resulted in a significant value of p = 0.000 (p < 0.05), indicating that lunge jump training improved the back kick technique of Kabaddi players in Central Java Province.